Mechanics, Structure and Evolution of Fault Zones - Ben-Zion, Yehuda.; Ben-Zion, Yehuda.; Sammis, Charles.; Sammis, Charles. (Pageoph Topical Volumes, 2010)
Considerable progress has been made recently in quantifying geometrical and physical properties of fault surfaces and adjacent fractured and granulated damage zones in active faulting environments. There has also been significant progress in developing rheologies and computational frameworks that can model the dynamics of fault zone processes. This volume provides state-of-the-art theoretical and observational results on the mechanics, structure and evolution of fault zones. Subjects discussed include damage rheologies, development of instabilities, fracture and friction, dynamic rupture experiments, and analyses of earthquake and fault zone data.